Bone metastasis: First manifestation of a hepatoma - Davidenko, Nicolás; Casanova, Marys; Silva García, Ernesto; De Los Santos, Julio (Cirugía del Uruguay, 1977)
In a case of hepatoma, the patient's first symptom was the presence of a voluminous costal tumor and biopsy showed that it was metastatic. Complementary tests indicated a hypervascular hepatoma with associated segmentary portal vein thrombosis, located in a parenchyma which seemed laparoscopically normal. Biopsy of primary tumor showed its histoarchitecture to be similar to that of metastases. A study of bibliography shows its raré occurrence and, when diagnosed, rapidly fatal evolution.